2021
DOI: 10.3390/agronomy11050962
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Quality Traits of Chickpea Genotypes under Rainfed Conditions in South Italy

Abstract: Chickpea (Cicer arietinum L.) is an important cool-season food legume crop that is mainly cultivated as a rainfed crop. This study was conducted in Italy between 2017 and 2019 to evaluate the stability of seed yield (SY), biomass (AGB) and 1000 seed weight (THS), and to assess the seed quality of 12 kabuli chickpea accessions under field conditions. The likelihood-ratio test revealed significant effects of genotype only for the SY and THS. The environment and genotype × environment interaction (GEI) effects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…The MTSI index enables simultaneous selection of genotypes based on performance and stability in terms of all of the traits and therefore is a unique index 7 . This index was used for selection of superior genotypes in Solanum melongena 41 , Brassica spp 42 , Chickpea 43 , maize 29 and rice 8 . MTSI protrudes as an effective tool to identify the strengths and weaknesses of genotypes and to select those with desired mean performance and stability.…”
Section: Discussionmentioning
confidence: 99%
“…The MTSI index enables simultaneous selection of genotypes based on performance and stability in terms of all of the traits and therefore is a unique index 7 . This index was used for selection of superior genotypes in Solanum melongena 41 , Brassica spp 42 , Chickpea 43 , maize 29 and rice 8 . MTSI protrudes as an effective tool to identify the strengths and weaknesses of genotypes and to select those with desired mean performance and stability.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the predicted selection benefits, assessing genetic progress may be an important method for improving crops. Several studies have shown that selection can effectively use available genetic variations with a certain degree of heritability to improve specific traits [26,57]. The concern of both heritability and genetic advance is more effective over the distinctively use of heritability.…”
Section: Genetic Componentsmentioning
confidence: 99%
“…The Smith-Hazel Index (SH index) is widely utilized in plant breeding as a multitrait selection index [26]. Reversing a phenotypic covariance matrix and a vector of economic weights is required to calculate the SH index.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations